PENDIDIKAN KECERDASAN MORAL SEBAGIA PENGUATAN KEPRIBADIAN SISIWA DI ERA DIGITAL SMAN 3 BULUKUMBA - Andrian; Andi sugiati; Herdianty R (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of moral intelligence education in strengthening students’ character in the digital era and to identify teachers’ strategies in instilling moral intelligence. The research employed a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The research subjects consisted of Civic Education (PPKn) teachers and the principal of SMAN 3 Bulukumba, while the research objects were students of Class XI.1. The findings revealed that students demonstrated a high level of empathy (100%) and a fairly good level of tolerance (75%), but showed lower levels in respect (55%) and fairness (53%). Teachers played a crucial role in instilling moral values through role modeling, digital ethics education, critical discussions, and the habituation of positive activities. This study emphasizes that moral intelligence education serves as a foundation for strengthening students’ character, enabling them to adapt to the challenges of the digital era.